2015
DOI: 10.1016/j.rasd.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Do communication and social interaction skills differ across youth diagnosed with autism spectrum disorder, attention-deficit/hyperactivity disorder, or dual diagnosis?

Abstract: Given the well-documented symptom overlap between Autism Spectrum Disorder (ASD) and Attention Deficit/Hyperactivity Disorder (ADHD), careful evaluation of potential differentiation and overlap is critical for accurate diagnostic decisions. Although research has considered the use of symptom checklists and parent/teacher report questionnaires for symptom differentiation, standardized observational methods, typically utilized in the context of ASD evaluation, have received less attention. The present study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…Variations in ADHD prevalence rates have been identified between US and non-US studies (Faraone et al ., 2003). As shown in Table 3, US studies (Grzadzinski et al ., 2011; Kotte et al ., 2013; Reiersen et al ., 2007; Salley et al ., 2015; Grzadzinski et al ., 2016; Zablotsky et al ., 2017) were identified to have a similar random pooled effect size to non-US studies (Ronald et al ., 2008; Kochhar et al ., 2011; Lichtenstein et al ., 2010; Russell et al ., 2014; Craig et al ., 2015; Green et al ., 2015; Jensen and Steinhausen, 2015). High levels of heterogeneity were identified in both US studies (78.61%) and non-US studies (89.86%), with US studies contributing to more of the heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in ADHD prevalence rates have been identified between US and non-US studies (Faraone et al ., 2003). As shown in Table 3, US studies (Grzadzinski et al ., 2011; Kotte et al ., 2013; Reiersen et al ., 2007; Salley et al ., 2015; Grzadzinski et al ., 2016; Zablotsky et al ., 2017) were identified to have a similar random pooled effect size to non-US studies (Ronald et al ., 2008; Kochhar et al ., 2011; Lichtenstein et al ., 2010; Russell et al ., 2014; Craig et al ., 2015; Green et al ., 2015; Jensen and Steinhausen, 2015). High levels of heterogeneity were identified in both US studies (78.61%) and non-US studies (89.86%), with US studies contributing to more of the heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to known differences, clinical and community samples studies were separated by sample type (Low et al, 2008). As seen in Table 3, studies that used a clinical sample (Luteijn et al, 2000;Mulligan et al, 2009;Kochhar et al, 2011;Kopp et al, 2011;Mayes et al, 2012;Kotte et al, 2013;Ayaz et al, 2014;Tye et al, 2014a;Craig et al, 2015;Salley et al, 2015) were identified to have a higher pooled mean difference than studies that used a community sample (Reiersen et al, 2007;Grzadzinski et al, 2011;van der Meer et al, 2012;van Steijn et al, 2014;Green et al, 2015). Confidence intervals indicate that the pooled mean difference between the two groups was not significant.…”
Section: Clinical V Community Adhd Samplesmentioning
confidence: 99%
“…Autistic trait measures have less specificity when applied to children with ASD and additional behavioral or emotional problems, including ADHD [ 98 , 99 ]; thus, it is possible that past reports of an association between ASD and ADHD traits were due to a systematic instrument bias, in which those with additional ADHD traits also receive higher ratings of autistic traits. The association between ADHD and ASD trait severity was noticeably absent in previous studies; however, when ASD traits were measured using measures such as the ADI-R, ADOS [ 38 , 47 , 48 , 75 ] or clinical symptom counts [ 74 ]. Unlike the SRS, which is parent questionnaire, measures such as the ADI-R and clinical symptoms involve clinical judgment, and in the case of ADOS, direct observation of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that 20–50% of children with ADHD have significant ASD characteristics even meet criteria for ASD ( Carpenter, Loo, Yang, Dang, & Smalley, 2009 ; Hattori et al., 2006 ). Research revealed that youth with combined ADHD and ASD have higher social interaction impairment than those with ADHD only ( Salley, Gabrielli, Smith, & Braun, 2015 ). However, the present study did not found the moderating effect of comorbid ASD on the association between social skills deficits and Internet addiction in adolescents with ADHD.…”
Section: Discussionmentioning
confidence: 99%